Susceptibility of several cotton varieties to the cotton flea beetle, Podagrica puncticollis Weise (Coleoptera: Chrysomelidae), in a hot dry tropical environment of Ethiopia - Abebe, Eshetu Agegnehu; BAYEH, Mulatu; TEBKEW, TEBKEW; MULATU, Wakgari (ENTOMOLOGIA HELLENICA, 2021)
Field trials were conducted to determine the reaction of cotton varieties to cotton flea beetle infestation. The experiment was laid out in a Randomized Complete Block Design with three replications comprising twelve cotton varieties. The results showed significant (P < 0.01) differences among varieties in the populations of adult beetle they hosted and the injury they sustained at 15, 22, 29, 36 and 43 days after sowing (DAS). At 15 DAS, the highest numbers of adult beetle per plant (6.3), percent leaf area damaged (60.32 %) and number of shot-holes per attacked leaf (53.4) was recorded in Cucurova variety, whereas the lowest in Bulk-202 (2.05 beetles, 26.15% leaf area damaged and 23.16 shot-holes). The rate of incidence and damages decreased with the increase of the age of the cotton plants. Significant differences were also observed among cotton varieties in some agronomic characteristics i.e. in number of plants counted per plot at harvest and seed cotton yield in terms of kilogram per hectare. Seed cotton yield obtained from all cotton varieties varied from 602.36 to 1644.71 kilogram per hectare and the highest was obtained from Bulk-202, while the lowest from Local variety. Based on these findings, Cucurova, Local, Ionia and Acala SJ-2 varieties showed highly susceptible response, while Candia, Sille-91 and Deltapine-90 were moderately susceptible to cotton flea beetle. However, Bulk-202, Delcero and Claudia were relatively more tolerant varieties followed by CCRI-12 and Cuokra. These results will be important for the most proper management of cotton flea beetle.